Effectiveness of an Educational Program in Enhancing Nurses’ Knowledge about Occupational Health Hazards - Hamad, Zaid; Qassim, Wessam (Iraqi National Journal of Nursing Specialties, 2019)
Objective: To determine the effectiveness of an Educational Program in Enhancing Nurse’s Knowledge about Occupational Health Hazards at Medical City Hospitals in Baghdad City.Methodology: The present study employed a quasi-experimental design held at Medical City Hospitals in Baghdad City. A non-probability sample (convenience sample) consisted of (60) nurse. Data were collected by using a self-report questionnaire which consisted of six parts (a) socio-demographic characteristics (b) physical hazards knowledge (c) chemical hazards knowledge (d) biological hazards knowledge (e) psychological hazards knowledge and (f) mechanical hazards knowledge. Data were analyzed using the statistical package for social science (SPSS) for windows Version 24.Results: There were statistically significant differences in nurses’ knowledge about occupational health hazards (physical hazards, chemical hazards, biological hazards, psychological hazards, and mechanical hazards) in the study group through posttest I, posttest II.conclusion: The occupational health hazards-based health education program was influential in enhancing nurses’ knowledge related to occupational health hazards.Recommendations: The researcher recommended the need to develop and carry out special educational programs for nurses to enhance their knowledge regarding occupational health hazards.